ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT PREDIKSI TINGKAT KEBANGKRUTAN PERUSAHAAN DENGAN MENGGUNAKAN MODEL ALTMAN : (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Dithalia Dewanti; Gusnardi Gusnardi; Mujiono Mujiono (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2022)
The economic crisis that occurred in 1997 until now has not been resolved. Many companies are experiencing financial difficulties that delay obligations that can lead to bankruptcy. Bankruptcy risk for a company can actually be seen and measured through financial statements to predict financial difficulties. The purpose of this study is to find out the potential level of bankruptcy of manufacturing companies listed on the Indonesia Stock Exchange based on the Altman Z-Score method for the period 2010-2019. This type of research is descriptively quantitative. Sampling uses purposive sampling techniques with a sample of 5 manufacturing companies of eating and beverage subsectors. The data analysis method used is altman Z-Score bankruptcy analysis. The results showed the percentage of companies potentially bankrupt by 30%, companies that entered in good health by 32%, and companies that were in grey area condition by 38%. Of the 5 companies, 3 companies have entered a potentially bankrupt condition with a z-score of less than 1.81, namely AkashaWira International Tbk, Prasida Aneka NiagaTbk and TigaPilar Sejahtera Food Tbk. Of the 5 companies 4 companies have entered the grey area where the company's Z-score value is between 1.81-2.99, namely AkashaWira International Tbk, Prasida Aneka NiagaTbk, Three Pillars of Sejahtera Food Tbk, and Indofood SuksesMakmurTbk. Only Ultrajaya Milk Industry & Trading Company Tbk has been in the healthy category for ten consecutive years where the company's Z-score value is always above 2.99.